2007
DOI: 10.1029/2007jd008999
|View full text |Cite
|
Sign up to set email alerts
|

Aircraft observations of dust and pollutants over northeast China: Insight into the meteorological mechanisms of transport

Abstract: [1] The meteorological mechanisms for lofting trace gases and aerosols out of the planetary boundary layer (PBL) into the free troposphere are key to understanding local air pollution problems as well as regional and global atmospheric chemistry and climate issues. Over the North American continent, convective storms and lifting in warm conveyor belts transport pollutants into the free troposphere. Little is known about the vertical distribution of pollutants and dust over east Asia, and the processes leading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
128
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(136 citation statements)
references
References 64 publications
3
128
1
Order By: Relevance
“…A recent study [Lee et al, 2009] applying GEOS-Chem simulated SO 2 and aerosol profiles suggests a seasonal average AMF of ∼0.5 over China. Validation against aircraft measurements over China [Dickerson et al, 2007;Xue et al, 2010] has shown that the operational OMI PBL SO 2 product can distinguish between clean and polluted conditions [Krotkov et al, 2008].…”
Section: Methodsmentioning
confidence: 99%
“…A recent study [Lee et al, 2009] applying GEOS-Chem simulated SO 2 and aerosol profiles suggests a seasonal average AMF of ∼0.5 over China. Validation against aircraft measurements over China [Dickerson et al, 2007;Xue et al, 2010] has shown that the operational OMI PBL SO 2 product can distinguish between clean and polluted conditions [Krotkov et al, 2008].…”
Section: Methodsmentioning
confidence: 99%
“…Asian mineral dust can be transported by the prevailing westerlies in the spring [e.g., Zhang et al, 1997], increasing particulate matter concentrations [e.g., Liu et al, 2006;Park et al, 2008] and pH values of rainwater [Wang et al, 2002] and cloud water in downwind areas. Aircraft observations through Asian outflow over the Asian continent [Dickerson et al, 2007] and the northwest Pacific Jordan et al, 2003;Maxwell-Meier et al, 2004], and in transpacific Asian plumes over the northeast Pacific [Andreae et al, 1988;Clarke et al, 2001;Price et al, 2003], have provided evidence of aerosol transport in the lower free troposphere. They reveal the spring months to be the time of maximum trans-Pacific transport of outflow and anthropogenic emissions associated with Asian dust, resulting in combined dust and pollution signatures in measurements of nominal air mass characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The physical processes behind the transport of gases from the planetary boundary layer into the free troposphere are crucial towards understanding air pollution problems at local and global scales as well as climate issues (Lelieveld and Crutzen 1990;Fadnavis et al 2011). Dickerson et al (2007) showed the role of cyclone in transporting pollutants into the UT from lower troposphere (LT) and reported the vertical exchange of ozone from lower stratosphere to UT. The tropopause height (TH) is also an important meteorological parameter that separates the troposphere from the stratosphere (Wirth 2001).…”
Section: Introductionmentioning
confidence: 99%